War on autism : on the cultural logic of normative violence - McGuire, Anne, 1981- (Ann Arbor : University of Michigan Press, 2016)
Examines acts of autism advocacy and how they create a perspective that views autism as a pathological biological disorder that is a threat to normative life, and as the means for normalizing, neutralizing, or eliminating the threat, creating advocacy that is?against? autism. She illustrates how these dominant discourses reveal autism as something to be fought and how this creates the possibility for acts of violence. She describes the emergence of autism as a category and how autism and advocacy have been tied together; how medical ideas of autism focus on bodies as deviant and in need of development, through red flag warning systems; the role of developmental time; strategies and targets of a culture at war with autism and similarities to the war on terror; and how the discourse of autism advocacy sees it as a thing and not a person, with analysis of the three murders of children with autism.
Machine generated contents note: 1. Delivering Disorder: Historical Perspectives on the Emergence of Autism and Advocacy in the West -- 2. Raising the Red Flags of Autism: Advocacy's Call to Arms -- 3. Act NOW: The S/pace of Advocacy in a Temporality of Urgency -- 4. "We Have Your Son ... ": Frames of Terror in Advocacy's War on Autism -- 5. Collateral Damage: Normalizing Violence and the Violence of Normalcy.
Includes bibliographical references and index.
Keywords: Autism -- Social aspects; Violence; Sociology of disability